APLIKASI PENJUALAN IKAN LELE PADA OESAPA LELE DENGAN PENERAPAN CUSTOMER RELANTIONSHIP MANAGEMENT - Tanesib, Yabeci; Saitakela, Mardhalia (Universitas Boyolali, 2018)
Oesapa Lele is a business entity established since 2015 which is managed by several people who aim to meet the needs of the people of NTT in meeting the need for catfish. Therefore it takes an application to help this business to run smoothly. The purpose of this research make online-based website application, in order to facilitate the process of purchasing catfish and the demand for catfish can be obtained easily and quickly so that the business process running smoothly without consumers or customers must come directly to Oesapa Lele. Data collection was done by literature study, observation and interview, and by applying the concept of customer relationship management (CRM). From the results of this study resulted in website applications that are expected to help the management of catfish Oesapa to perform the process of selling catfish transactions.